Tribological characteristics of micro-ball bearing with V-shaped grooves coated with ultra-thin protective layers. (March 2018) - Oh, Dae-San; Kang, Kyeong-Hee; Kim, Hyun-Joon; Kim, Jae-Kang; Won, Moon-Sub; Kim, Dae-Eun
Abstract: The tribological characteristics of micro-ball bearing comprising Si substrate with V-shaped grooves applied with various types of thin films were investigated. Self-assembled monolayers and metallic thin films were deposited on the Si substrate to enhance the tribological characteristics. Experiments were conducted for 100 and 2000 cycles to estimate initial frictional behavior and durability of micro-ball bearing, respectively. It was demonstrated that both metallic thin films and self-assembled monolayers effectively reduced the friction coefficient and extended the lifetime of the micro-ball bearing. Particularly, self-assembled monolayer exhibited more stable frictional characteristics and longer lifetime compared to metallic thin films. Highlights: Investigation of micro-ball bearing with V-shaped grooves coated with protective layers was conducted. In case of Ag coating for V-groove, thin Ag film (33 nm) provided higher lubrication effect than thick Ag film (126 nm). OTS-SAM coated V-shaped groove recorded the lowest friction coefficient value with 0.0076. For micro-ball bearing, OTS-SAM coating are provides notable resistance of friction and wear.